THE IMPLEMENTATION OF DISCUSSION-BASED LEARNING THROUGH E-LEARNING IN CIVIC EDUCATION SUBJECTS - Hanny Rahayu; Lenny Kristianti; Farhan Rachmansyah; Sitti Nur Aisyah (TOPLAMA, 2026)
This study analyzes the implementation of the discussion-based learning method in e-learning for the civic education subject in the eleventh grade of the computer and network engineering program at Bina Insan Bangsa Vocational High School, West Bandung Regency. The research employs a qualitative approach with a descriptive method. The findings indicate that the implementation of the discussion-based learning method through e-learning involves distance learning without direct face-to-face interaction between teachers and students, conducted via the internet using communication technology. E-learning serves as a platform for applying the discussion-based learning method, facilitating interaction both between teachers and students as well as among students themselves. As a result, the use of e-learning has proven effective in supporting the teaching and learning process.